The Effect of Capital Adequacy Ratio, Loan to Deposit Ratio, and Operational Costs than Operating Revenue on Return on Assets: Study on Conventional Banks in Indonesia - Muhammad Herizal; Diana Diana; Rezti Rezti; Sri Suryani (PT. Hanken SUkses Jaya, 2022)
This study aims to determine the effect of Capital Adequacy Ratio (CAR) and Operating Income Operating Costs (BOPO) on Profitability Return On Assets (ROA) in conventional banks in Indonesia. The data obtained is sourced from financial statements listed on the Indonesia Stock Exchange for the period 2013–2017. Data analysis was carried out using quantitative descriptive statistical methods. From this study, it can be concluded that the results of the Simultaneous Test show that CAR, LDR, and BOPO have a significant simultaneous effect on ROA at conventional banks in Indonesia in 2017 and CAR and BOPO have a partially significant effect on ROA at banks. conventional method in Indonesia in 2017. LDR has no effect on ROA.